2022
DOI: 10.3389/fenrg.2021.802398
|View full text |Cite
|
Sign up to set email alerts
|

Solvation, Rational Design, and Interfaces: Development of Divalent Electrolytes

Abstract: Rechargeable multivalent ion batteries are promising tools to complement current lithium-ion batteries for a future of diverse energy storage needs. Divalent Mg and Ca are attractive candidates for their high crustal abundance, high volumetric anode capacity, and infrequent dendrite formation during electrochemical cycling. Electrolyte research is central to these efforts and continually improves coulombic efficiencies towards the ideal 100%. This mini-review discusses recent work towards fundamental understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The initial Mg battery prototype, reported in 2000, instigated extensive research in the subsequent decades, specifically directed toward increasing the achievable energy density of the systems by developing novel electrolytes, cathodes, and interfacial chemistry. Viable electrolytes, which demonstrate a broad and stable electrochemical window while maintaining chemical compatibility with the anode and cathode materials, are recognized as a long-term challenge for realizing high voltage (i.e., >3.0 V vs Mg 2+ /Mg 0 ) multivalent cation energy storage …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial Mg battery prototype, reported in 2000, instigated extensive research in the subsequent decades, specifically directed toward increasing the achievable energy density of the systems by developing novel electrolytes, cathodes, and interfacial chemistry. Viable electrolytes, which demonstrate a broad and stable electrochemical window while maintaining chemical compatibility with the anode and cathode materials, are recognized as a long-term challenge for realizing high voltage (i.e., >3.0 V vs Mg 2+ /Mg 0 ) multivalent cation energy storage …”
Section: Introductionmentioning
confidence: 99%
“…Liao et al established that the anode−electrolyte interface characteristics are influenced by the solvated structures of Mg 2+ , resulting in substantial variations in electrochemical performances. 10 Subsequent studies focused on regulating the interface composition through modifications in electrolyte solvation by the addition of chelating additives. Hou et al demonstrated that methoxyethyl-amine enables engineering and solvation sheath reorganization for reducing parasitic reactions and enhancing the reversibility of Mg-based electrochemical systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the development of useful electrolytes, exhibiting a wide electrochemical window with suitable compatibility with anode and cathode materials, is still very limited. Years of fundamental studies have shown that the electrolyte properties such as conductivity, viscosity, solvation structure, and chemical stability greatly affect the electrochemical performance (Deivanayagam et al, 2019;Leon et al, 2022) and are highly dependent on the exact formulation and a complex interaction between solvents and salts. With these constraints, only a few solvents meeting the requirements are currently practical in terms of their ability to dissociate Mg (or Zn and Ca) salts and show reversible metal plating and stripping processes (Bitenc et al, 2019;Deivanayagam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Complementary to discovering a direct LIB replacement is the concept of diversifying rechargeable battery chemistries that can be customized for specific applications, such as long-duration energy storage systems and various transportation modes like aviation, rail, and ships. 1 These discussions have fueled the surge in "beyond LIB" research. 2 Alkaline earth metal-based battery (Mg, Ca) literature offers the advantages of crustal abundance, volumetric density, and overall safety, with a considerably higher focus on Mg electrolyte development.…”
mentioning
confidence: 99%